Orientación vocacional, primer ingreso de carrera, y sexo en el MMPI - Navarro, Roberto (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study investigated possible differences between three groups of male and female College students: Vocational Guidance (O.V.), First Admission to College (P.I.), and those who Change their Major (C.C.). For all comparisons, the MMPI Basic Scales, the Content Scales, and six Indices were used. Data were analyzed through ANOVA (2 x 3 with three Group levels and two Sex levels). Additional Duncan’s tests between Group levels were also made. A total of 180 subjects was selected (90 males and 90 females), with ages ranging from 18 to 2 1 years.